2022
DOI: 10.1002/jpen.2432
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality of enteral formulations handled at home: A systematic review

Abstract: Background Studies have shown an increase in the number of patients who use enteral nutrition at home and the benefits of this type of nutrition care. However, little is known about the risk of bacterial contamination of enteral formulations prepared at home. Therefore, the aim of the study was to assess the microbiological quality of home‐prepared enteral formulations. Methods This study is a systematic review, registered in PROSPERO. The search for articles was carried out in databases and gray literature. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…9 However, in Brazil, the blenderized formulas are classified according to their composition: Homemade enteral preparations (HEPs) are made exclusively with foods such as vegetables, cereals, legumes, milk, etc; CEFs are chemically prepared in powder form for reconstitution with water or semiready liquids and liquids in sterile packaging ready for use; and blended enteral preparations (BEPs) are composed of foods with the addition of CEF. [9][10][11][12][13][14] Enteral formulations can be infused by bolus, by infusion pump, or through the gravitational method. 3,15 Materials, such as bottles, syringes, and feeding bags, for enteral nutrition can be used to administer the formulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 However, in Brazil, the blenderized formulas are classified according to their composition: Homemade enteral preparations (HEPs) are made exclusively with foods such as vegetables, cereals, legumes, milk, etc; CEFs are chemically prepared in powder form for reconstitution with water or semiready liquids and liquids in sterile packaging ready for use; and blended enteral preparations (BEPs) are composed of foods with the addition of CEF. [9][10][11][12][13][14] Enteral formulations can be infused by bolus, by infusion pump, or through the gravitational method. 3,15 Materials, such as bottles, syringes, and feeding bags, for enteral nutrition can be used to administer the formulations.…”
Section: Introductionmentioning
confidence: 99%
“…1,9,11 The closed system, with the use of ready-to-hang liquid and sterile CEFs, is most recommended, as it does not require prior handling and presents a lower risk of contamination. 1,4 However, this system makes it difficult to individualize the dietary prescription and does not correspond to the reality experienced in the households of several developing countries, such as Brazil, 9,14,16 as it represents an expensive and difficult alternative for patients, especially those with low income. [17][18][19] Thus, the open administration system, especially with the use of HEPs and BEPs, remains a viable alternative for patients who require this type of nutrition care.…”
Section: Introductionmentioning
confidence: 99%
“…16,20,21 A recently published systematic review study on the risk of bacterial contamination of enteral formulations prepared at home showed that 72.81% of the 217 enteral formulations analyzed had unsatisfactory microbiological quality, indicating poor hygiene conditions during food handling. 22 Other studies have also demonstrated the contamination of enteral formulations due to errors in preparation and storage. 6,16,18 Particular emphasis has been placed on handwashing errors 16,23 ; inadequate procedures for cleaning and sanitizing equipment, utensils, and surfaces 16,21,23 ; and improper storage conditions for ready-to-use enteral formulations.…”
Section: Introductionmentioning
confidence: 99%
“…6,16,18 Particular emphasis has been placed on handwashing errors 16,23 ; inadequate procedures for cleaning and sanitizing equipment, utensils, and surfaces 16,21,23 ; and improper storage conditions for ready-to-use enteral formulations. 21 In addition, studies have also shown that regardless of the characteristics of the enteral formulations used by patients at home, most ready-to-use enteral formulations had unsatisfactory microbiological quality, 16,22 which demonstrates the risk of outbreaks of foodborne diseases (FBDs) associated with enteral formulations handled at home.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation